Megalomma Johansson, 1925 (Polychaeta: Sabellidae) from America and other world-wide localities, and phylogenetic relationships within the genus - Tovar-Hernández, María Ana; Carrera-Parra, Luis F. (Zootaxa, 2011)
The present study deals with the revision of type and non-type material from 14 species of Megalomma Johansson, 1925 (Polychaeta: Sabellidae) which have been described from America: M. bioculatum (Ehlers, 1887), M. carunculata Tovar-Hernández and Salazar-Vallejo, 2008, M. circumspectum (Moore, 1923), M. coloratum (Chamberlin, 1919), M. fauchaldi Giangrande, Licciano and Gambi, 2007, M. gesae Knight-Jones, 1997, M. heterops Perkins, 1984, M. lobiferum (Ehlers, 1887), M. modestum (de Quatrefages, 1866), M. pacifici (Grube, 1859), M. perkinsi Tovar-Hernández and Salazar-Vallejo, 2006, M. pigmentum Reish, 1963, M. roulei (Gravier, 1908b) and M. splendidum (Moore, 1905); five from other world-wide localities: M. acrophthalmos (Grube, 1878), M. claparedei (Gravier, 1908a), M. lanigera (Grube, 1846), M. mushaense (Gravier, 1908a), M. sp.; and the formal description of a new species: Megalomma georgiense n. sp., from USA. The genus Megalomma was amended based on radiolar, peristomial and chaetal features. Megalomma roulei (Gravier, 1908b) is declared incertae sedis. Megalomma clara (Chamberlin, 1919) is synonymized with M. coloratum (Chamberlin, 1919). Megalomma pigmentum Reish, 1963 and M. monoculata Hartmann-Schröder, 1965 are cryptic. A key is included to the American species of Megalomma. A cladistic analysis was conducted based on examination of type material from the species reviewed in this study and from twelve species based on original descriptions (M. cinctum Fitzhugh, 2003, M. inflata Capa & Murray, 2009, M. interrupta Capa and Murray, 2009, M. kaikourense Knight-Jones, 1997, M. messapicum Giangrande and Licciano, 2008, M. miyukiae Nishi, 1998, M. multioculatum Fitzhugh, 2002, M. nechamae Knight-Jones, 1997, M. phyllisae Capa and Murray, 2009, M. trioculatum Reish, 1968, M. quadrioculatum (Willey, 1905) and M. vesiculosum (Montagu, 1815)). The phylogenetic reconstruction of Megalomma using parsimony analysis of 32 morphological characters yielded 26 equally most parsimonious trees (CI= 0.38, RI= 0.56). The hypotheses by Capa and Murray (2009) that considered species with dorsal collar margins fused to the faecal groove (Knight-Jones’s group 1) as part of an apomorphic clade, and those with dorsal collar margins unfused to the faecal groove (Knight-Jones’s group 2) as plesiomorphic, are not supported in this present study. In our analysis, species nested in group 2 comprises one of the most derived clades, while the clade containing species of group 1 was not recovered. DNA barcoding of M. coloratum, M. lobiferum and M. carunculata is included.